The Role of Informal Education in the Formation of Children's Character - Dina Septima; Rina Restiana; Ila Aisyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to describe and analyze the role of informal education in the formation of children's character. The research method applied in this article is to use a qualitative research method, which is a research method that focuses on understanding social phenomena that occur in society. Character building and character education is a necessity, because education not only leads the nation's children to be intelligent but also to have good character and manners, so that their existence as members of society becomes meaningful both for themselves and for society in general. This means, by attaching these behavioral indicators to every child of the nation in the education process, as as mentioned in the goals of national education above, it has reflected an individual figure of character. Results of this research 1). Giving Islamic religious lessons, 2). Training children to carry out worship, 3). provide encouragement for learning, 4). Facilitate children's learning activities, 5). Accompanying children during learning activities, 6). Supervise and direct children's interactions with their peers, and 7). Guiding children by example in worship.